Social Awareness of the Circular Economy as an Integral Part of Sustainable Development. Observations from Poland - Lewandowska, Aleksandra; Rogatka, Krzysztof; Lopata, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sustained growth in the number of urban dwellers means that matters concerning the development of modern cities are not only a challenge for current residents, but a global test for the entire population. The purpose of this paper is to analyze and assess social awareness regarding sustainable development, with particular emphasis on matters concerning the circular economy.
Keywords: sustainable development; eco-development; closed loop; smart city; responsibility; zrównoważony rozwój; ekorozwój; pętla zamknięta; inteligentne miasto; odpowiedzialność